PENGUATAN PERAN PROFESI PUSTAKAWAN DALAM MENINGKATKAN LITERASI MASYARAKAT - Hardianty, Sri; Muliardi, Randi; Maulinda, Irma; Gunawan, Nazali (LPPM Universitas Bina Bangsa, 2024)
Increasing public literacy in today's digital information age demands a more complex and adaptive role for librarians. This seminar aims to strengthen the understanding of the roles and challenges faced by librarians and to increase their confidence through a process of reflection. Librarians not only function as book collection managers, but also as information access facilitators, digital literacy developers, and guides in navigating the world of information. The main challenges faced include changes in user behavior, developments in information technology, competition with digital services, lack of resources, and lack of appreciation for the profession. Through this online seminar, participants were given an in-depth understanding of the challenges librarians face and strategies to deal with them, including continuous competency development, raising public awareness, and using the latest technology. Self-reflection was also emphasized as a method to increase librarians' confidence and effectiveness. The results of the seminar showed that there was an increased understanding by participants of the role of librarians and the challenges they face, as well as improved confidence and skills. Suggestions include competency development, infrastructure improvement, and advocacy of the librarian profession to ensure their relevance and contribution in improving community literacy.